Examining the Role of Financial Literacy, Cognitive Bias, and Emotional Bias in Shaping Investment Decisions : A Study on the Indonesian Stock Exchange - Bahari, Samsul; Zarliani, Wa Ode Al; Suriadi,; Hasddin, (Indian Journal of Finance, 2025)
Objective : This study, motivated by the desire to identify the influence of emotional and cognitive biases on financial literacy and investment choices, explored the role of financial information as a mediator of biases (cognitive and emotional) in understanding investment decision-making. Methods : An explanatory quantitative approach was used to study the behavior of individual investors listed on the Indonesia Stock Exchange. Data of 376 investors were obtained through a simple random sampling method. Structural equation modeling was performed using PLS-SEM. Findings : The discoveries uncovered that money management knowledge was one of the main factors that profoundly influenced investment decisions. It also intervened as a moderator in the relationship between cognitive and emotional biases and investment choices. The study additionally revealed that cognitive biases weakened investment decisions and increased financial knowledge. At the same time, emotional biases obstructed financial knowledge, despite supporting investment decisions. Practical Application : The study, which mainly focused on recognizing and limiting biases, could assist investors in straightforward decision-making. Besides, they pointed out the importance of the financial education sector, thus giving policymakers the necessary information to design programs that help increase the investors’ financial literacy level. Originality : This study extended the realm of behavioral finance by exploring the mediating influence of financial literacy amid cognitive and emotional biases on investment decisions within the Indonesian stock market. Thus, it enhanced comprehension of investor conduct in such emerging economies.